2008
DOI: 10.1159/000112458
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Determinants of the Metabolic Syndrome

Abstract: The metabolic syndrome has attracted interest because of its relevance to major contemporary chronic diseases associated with inactive lifestyles and the abundance of food, both of which have resulted in a way of life which challenges our genetic makeup. Changing the fuel mix by the introduction of more monounsaturated and polyunsaturated fatty acids, a reduction in saturated fatty acids, an increase in fiber, and the use of low glycemic index slow-release carbohydrate foods may make a difference, as will incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 140 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…The use of supplements was controlled for the potential impact of the dietary supplement on vitamin K intake and status. The final multivariate model included additional dietary factors such as intakes of fiber, total fat, polyunsaturated fat, saturated fat, total carbohydrate, and total energy, which have been shown to be related to MetS as reviewed by Josse [21]. For each logistic regression model, a separate analysis was carried out, excluding subjects who had taken supplements during the past month.…”
Section: Discussionmentioning
confidence: 99%
“…The use of supplements was controlled for the potential impact of the dietary supplement on vitamin K intake and status. The final multivariate model included additional dietary factors such as intakes of fiber, total fat, polyunsaturated fat, saturated fat, total carbohydrate, and total energy, which have been shown to be related to MetS as reviewed by Josse [21]. For each logistic regression model, a separate analysis was carried out, excluding subjects who had taken supplements during the past month.…”
Section: Discussionmentioning
confidence: 99%
“…Known risk factors for metabolic syndrome include age, obesity, diet, dietary patterns across life stages, and lack of exercise with variation in the prevalence observed across gender and ethnic groups (Park et al, 2003; Josse et al, 2008; Otsuka et al, 2010; Li et al, 2011; Beltran-Sanchez et al, 2013). Current smoking has been associated with the presence of insulin resistance, diabetes and metabolic syndrome (Facchini et al, 1992; Will et al, 2001; Park et al, 2003; Weitzman et al, 2005) whereas alcohol consumption appears to be protective to some extent (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the benefits to patients with metabolism-related disorders of restricted dietary calories (Azadbakht, Mirmiran, Esmaillzadeh, Azizi, & Azizi, 2005;Josse, Jenkins, & Kendall, 2008;Konig, Deibert, Frey, Landmann, & Berg, 2008) and increased intake of certain macronutrients (Flachs, Rossmeisl, & Kopecky, 2014;Gadgil et al, 2013;Rizza et al, 2009), particularly n-3 longchain polyunsaturated fatty acids (LC-PUFA). de Mello et al (2011) reported that MetS patients who consumed a healthy diet that included fatty fish and wholegrain products for 12 weeks had reduced levels of markers of inflammation and endothelial dysfunction, such as plasma E-selectin and highsensitivity C-reactive protein (hsCRP) (de Mello et al, 2011;Su, Lee, Cheng, & Huang, 2014).…”
Section: Introductionmentioning
confidence: 99%